Techno-economic analysis of freight railway electrification by overhead line, hydrogen and batteries: Case studies in Norway and USA. (August 2020) - Zenith, Federico; Isaac, Raphael; Hoffrichter, Andreas; Thomassen, Magnus Skinlo; Møller-Holst, Steffen
Two non-electrified railway lines, one in Norway and the other in the USA, are analysed for their potential to be electrified with overhead line equipment, batteries, hydrogen or hydrogen-battery hybrid powertrains. The energy requirements are established with single-train simulations, including the altitude profiles of the lines, air and rolling resistances, and locomotive tractive-effort curves. The composition of the freight trains, in terms of the number of locomotives, battery wagons, hydrogen wagons, etc. is also calculated by the same model. The different technologies are compared by the criteria of equivalent annual costs, benefit–cost ratio, payback period and up-front investment, based on the estimated techno-economic parameters for years 2020, 2030 and 2050. The results indicate the potential of batteries and fuel cells to replace diesel on rail lines with low traffic volumes.